Distributed Storage for the Provision of Ancillary Services to the Main Grid: Project PRESTO. (November 2016) - Nassuato, S.; Magistrati, G.; Marchegiani, G.; Brivio, C.; Delfanti, M.; Falabretti, D.; Merlo, M.
Abstract: This paper presents the three-year PRESTO research project (2013-2015). PRESTO is a self-funded project developed by the Department of Energy of Politecnico di Milano in cooperation with FIAMM Storage, Elvi Energy and MCM Energy Lab (an Italian spin-off). Within the project, experimental tests and numerical simulations were performed in order to evaluate the effectiveness of an Energy Storage System (ESS) in the provision of ancillary services to the main grid. This paper focuses specifically on the experimental and numerical analyses carried out in the project to develop an innovative control law for the primary frequency regulation, able to maximize the performances of the regulating service and effectively manage the ESS state of charge.